Misled by the Xpert-Kikuchi’s disease masquerading as tuberculosis - Krishnakumar, Aparna; Sivaprakasam, Elayaraja; Ravichandran, Latha; Pasupathy, Umapathy; Premkumar, Sarala; Mohan, Ram (International Journal of Contemporary Pediatrics, 2020)
Kikuchi-Fujimoto disease (KFD), also called histiocytic-necrotizing lymphadenitis is a rare, idiopathic and self-limiting cause of lymphadenitis. Clinical presentation of KFD closely resembles nodal tuberculosis (TB). Here we present a case of an adolescent female whose diagnosis of KFD was made despite being misled in the course. A 15-year-old female, previously treated for tuberculous lymphadenitis was brought with complaints of fever for 1 month. Various possibilities considered were TB reactivation, autoimmune disorders, lymphoma. Lymph node biopsy for gene Xpert showed TB bacilli detected but low with no RIF resistance. Despite anti tuberculous treatment initiation, there was no improvement in the clinical condition. Histopathology of cervical node showed features of Kikuchi lymphadenitis. Literature search revealed that gene Xpert can detect the intact DNA of Mycobacterium tuberculosis even years after the previous treatment. On stopping anti tuberculosis therapy (ATT) and starting IV steroid, she started improving dramatically. KFD should always be kept as a differential diagnosis in any individual with fever and lymphadenopathy. Diagnosis can be misled in any patient based on gene Xpert reports alone which often turns out to be positive if there is past history of TB as gene Xpert detects DNA from non-intact cells suggesting that dead bacilli contribute to the false positivity.